A modified multilevel approach to the dynamic hierarchical clustering for complex types of shapes - Shatovska, Tetyana; Onoprienko, Oksana; Fedorov, Artem (Eastern-European Journal of Enterprise Technologies, 2012)
In this paper we present a modified hierarchical clustering algorithm that used the main idea of Chameleon and the effectiveness of suggested approach will be demonstrated by the experimental results